STEM Activity Manager Application with Dual Authentication using One Time Password (OTP) - RIDUAN, MUHAMAD AIMAN; AHMAD KHALID, DR SHAMSUL KAMAL (Applied Information Technology And Computer Science, 2023)
STEM education is needed to produce quality and sufficient human capital in STEM to drive the economy. In UTHM there is a STEM committee that is to promote STEM among middle and lower form schools. However, FSKTM STEM committee does not yet have a computerized system to manage STEM activities. The application system is developed using the prototype SDLC method using Thunkable, Airtable. The proposed application is an activity manager that can store, edit, update activities. The system is developed and is then tested for any bugs and passed the criteria. The systems advantages and disadvantages are it can save activity and users and list them.